Run to the Sound of the Guns : The True Story of an American Ranger at War in Afghanistan and Iraq /: The True Story of an American Ranger at War in Afghanistan and Iraq. (2018) - (Platoon sergeant), Moore, Nicholas; Bahmanyar, Mir
No abstract available